Implementation Of the People's Market Application to Improve the Performance of MSMES In Kendal Regency: Integration of Theory Acceptance Model (TAM) And Extended Theory of Planned Behavior (TPB) - Eka Kurnia Patmasari; Haifa Hannum Arija (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
ABSTRACT The emergence of Covid 19 has devastated the performance of Micro, Small and Medium Enterprises (MSMEs) including in Kendal Regency. Through the People's Market application, it is hoped that it can encourage the performance of MSMEs after the pandemic. However, the problem that occurs is that users of the People's Market application in MSME players are still low which can hinder growth and competitiveness in the digitalization era. This study aims to analyze the behavior of MSME players in adopting the People's Market application in Kendal Regency through the integration of the Theory Acceptance Model (TAM) and the Extended Theory of Planned Behavior (TPB). This research is a causality study using seven main variables tested from the TAM and TPB models, namely: perceived benefits; perceived ease of use; attitude in adopting the People's Market application; subjective norms; perceived behavioral control; behavioral intention in adopting the People's Market application; and actual behavior. The sample of this study used a purposive sampling method with a total sample that met the criteria of 231 respondents. The data was obtained from distributing questionnaires via google form. The data were statistically tested through the AMOS program. The results showed that perceived benefits and perceived ease of use affect attitudes. Attitude affects the behavioral intention of traders in adopting the People's Market application. However, subjective norms and perceived behavioral control have no significant effect on behavioral intentions. The results also prove that behavioral intentions can encourage merchants to carry out actual behavior in adopting the People's Market application.